SAT0440 New Data on Renal Crisis and Predictive Markers from More Than 3000 Patients. (9th June 2015) - Moinzadeh, P.; Riemekasten, G.; Fierlbeck, G.; Henes, J.; Blank, N.; Melchers, I.; Mueller-Ladner, U.; Kreuter, A.; Susok, L.; Guenther, C.; Zeidler, G.; Pfeiffer, C.; et al.
Abstract : Background: To improve detection and follow-up of patients with systemic sclerosis, the German Network for Systemic Scleroderma (DNSS) was founded 2003 and comprise rheumatologists, dermatologists, pulmonologists and nephrologists from more than 40 medical centers. Renal crisis is rare but still a medical emergency in patients with SSc. Objectives: Up to date, more than 3000 patients have been grouped into four descriptive disease subsets, i.e. limited cutaneous disease (lcSSc), diffuse cutaneous disease (dcSSc), overlap-syndrome and undifferentiated connective tissue disease (UCTD) with scleroderma features. Methods: In this analysis, we have focused on renal crisis within the three main subsets, e.g. lcSSc, dcSSc and overlap-syndromes to identify baseline aspects, which are predictive for future SSc associated renal crisis. Results: Recent analyses of up to now 3180 patients revealed that 56% of patients suffer from limited SSc (lcSSc), 34% from diffuse SSc (dcSSc) and 11% of patients were diagnosed with an overlap-syndrome. Eighteen patients developed a renal crisis (1.4%, 18/3180), while 10% (315/3180) were classified with kidney involvement and 8% (257/3180) with proteinuria. Of these, 66.7% (12/18) were diagnosed with the diffuse form of SSc, while just 27.8% (5/18) were diagnosed with lcSSc and 5.6% (1/18) with SSc-overlap syndromes. Predictive factors for renal crisis in our patient cohort included the diffuse form of SSc (odds ratio (OR) 4.6, p=0.005, 95%>confidence interval (CI) 1.6-13.5), a modified Rodnan skin score (mRSS) of more than 15 (OR 4.7; p=0.002, 95%>CI 1.7-13), positive anti-RNA polymerase (RNAP) autoantibodies (OR 24.6, p<0.0001, 95%>CI 6.1-99.5), tendon friction rubs (OR 5.4, p=0.004, 95%>CI 1.7-16.9), hypertension (OR 6.1, p<0.0001, 95%>CI 2.3-16.5), proteinuria (OR 11.8, p<0.0001, 95%>CI 4.3-32.1) and elevated CK-levels (OR 5.1, p=0.01, 95%>CI 1.4-18.9). Interestingly, positive anti-topoisomerase autoantibodies did not predict a higher risk for renal crisis. Patients diagnosed with renal crisis were significantly more frequent on ACE-inhibitors (61.1%, 11/18, p=0.001). Of these, 5 patients also suffered from proteinuria and 7 patients from hypertension. Patients on systemic glucocorticoids had also an increased risk to develop a renal crisis (OR 5.1, p=0.002, 95%>CI 1.8-14.3), independent of the dosage (> or <7.5mg/day). Conclusions: Renal crisis has become a rare complication in SSc. The highest risk was associated with the detection of RNAP antibodies, followed by proteinuria, hypertension, tendon friction rubs, elevated CK-levels and a modified Rodnan skin Score above 15. Close monitoring of patients at high risk for SSc associated renal crisis is mandatory. Disclosure of Interest: None declared